Sistem pakar mendiagnosa penyakit kolesterol berbasis database dan web - Aswadul Fitri Saiful Rahman; puja indriani; mayda waruni kasrani (Lembaga Penelitian Universitas Balikpapan, 2019)
Technological advancements, increasing various aspects of life in the modern era have changed the style and pattern of people's lives. Unhealthy lifestyles are clearly seen in big cities, seen from food that can be found in every fast food restaurant or fast food. If the diet is not controlled, a person will be more susceptible to diseases that are difficult to cure, namely cholesterol. In this study the authors aim to design an expert system application that is used to diagnose cholesterol based and web- based cholesterol diseases based on the symptoms of the disease felt by patients who become a decision in the form of a level of confidence and the solution by using the forward chaining method to get forward reasoning and calculate the value of trust of the symptoms chosen by the patient.